An Exploration of the Leadership Behaviours and Attitudes Employees Most Value During a Crisis: A Case Study of Academics in Remote Work During COVID-19 - Josiah, Kelly (Department of Social Development, 2023)
The COVID-19 pandemic has had a substantial impact on organisations and the workforce, globally and in South Africa more specifically. This is true in many sectors, including that of higher education, where the economic, social, and psychological impacts of the pandemic are indisputable. However, it can be argued that organisational leaders have played a significant role in assisting employees to navigate the uncertainty of the events since March 2019. The primary aim of this research is to explore the leadership behaviours and attitudes most valued by academics at a residential university in South Africa. Secondary aims of the study focus on academics' experiences of well-being while working remotely during COVID-19. An exploratory case study design within the interpretivist paradigm was used, with academics at a residential university in South Africa as the case under study. Therefore, the unit of analysis is the individual. Purposive and snowball sampling strategies were adopted, and a total of 15 participants were interviewed. Inductive and deductive approaches were used to analyse the data using Braun and Clarke's (2006) six-step Thematic Analysis technique. Two primary themes emerged during analysis of the data: (1) human-centric leadership; and (2) self-care and self-management. Each primary theme had a number of associated secondary and tertiary themes. The results identified the leadership behaviours and attitudes that the sample found most valuable in the transition to remote working. Along with this, the various coping strategies used by academics in the sample are noted. For example, the sample expressed their appreciation for leaders who adapted their behaviour and attitude to suit the COVID-19 context. Participants appreciated human-centric leadership behaviours and attitudes that were kind and caring, taking into account academics' various realities. Further results demonstrate that academics employed coping strategies, such as healthy lifestyle choices to maintain their overall well-being and leveraged professional and personal support networks to effectively transition to the remote working context.